PENGARUH KOMPLEKSITAS TUGAS, LOCUS OFF CONTROL, TEKANAN KETAATAN, SIKAP PROFESIONALISME DAN GENDER TERHADAP AUDIT JUDGMENT (Studi Empiris Pada Kantor Akuntan Publik di Kota Semarang) - Stevani DivaCindi Putri, 13.05.52.0126; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2018)
Auditors are person who conduct an audit of financial statements, to carry out the task required an audit judgment. This study examined the effect of task complexity, locus off control, obedience pressure, professionalism and gender toward audit judgment. This research is a quantitative research, which uses primary data in the form of questionnaires to collect data. Respondents in this research are auditors who work in Public Accountant Offices (KAP) in Semarang. The sampling technique is convenience sampling which 60 auditors are participated of 10 Public Accountant Offices (KAP). Data were analyzed using SPSS version 24. The results of this research indicate that task complexity, locus off control, and professionalism have a significant effect on audit judgment, while the obedience pressure and gender do not affect audit judgment. Keywords :Task Complexity, Locus Off Control, Obedience Pressure, Professionalism, Gender, Audit Judgment.